Carbon, nitrogen, and oxygen stable isotopes in modern tooth enamel: A case study from Gorongosa National Park, central Mozambique - Lüdecke, Tina; Leichliter, Jennifer N.; Aldeias, Vera; Bamford, Marion K.; Biro, Dora; Braun, David R.; Capelli, Cristian; Cybulski, Jonathan D.; Duprey, Nicolas N.; Ferreira da Silva, Maria J.; Foreman, Alan D.; Habermann, Jörg M.; et al. (Frontiers in Ecology and Evolution, 2022)
The analyses of the stable isotope ratios of carbon (δ13C), nitrogen (δ15N), and oxygen (δ18O) in animal tissues are powerful tools for reconstructing the feeding behavior of individual animals and characterizing trophic interactions in food webs. Of these biomaterials, tooth enamel is the hardest, most mineralized vertebrate tissue and therefore least likely to be affected by chemical alteration (i.e., its isotopic composition can be preserved over millions of years), making it an important and widely available archive for biologists and paleontologists. Here, we present the first combined measurements of δ13C, δ15N, and δ18O in enamel from the teeth of modern fauna (herbivores, carnivores and omnivores) from the well-studied ecosystem of Gorongosa National Park (GNP) in central Mozambique. We use two novel methods to produce high-precision stable isotope enamel data: (i) the ‘oxidation-denitrification method’ which permits the measurement of mineral-bound organic nitrogen in tooth enamel (δ15Nenamel), which until now, has not been possible due to enamel’s low organic content, and (ii) the ‘cold trap method’, which greatly reduces the sample size required for traditional measurements of inorganic δ13Cenamel and δ18Oenamel (from ≥0.5 to ≤0.1 mg), permitting analysis of small or valuable teeth and high-resolution serial sampling of enamel. The stable isotope results for GNP fauna reveal important ecological information about trophic level, dietary niche, and resource consumption. δ15Nenamel values clearly differentiate trophic level (i.e., carnivore δ15Nenamel values are 4.0 ‰ higher, on average, than herbivores), δ13Cenamel values distinguish C3 and/or C4 biomass consumption, and δ18Oenamel values reflect local meteoric water (δ18Owater) in the park. Analysis of combined carbon, nitrogen and oxygen stable isotope data permit geochemical separation of grazers, browsers, omnivores and carnivores according to their isotopic niche, while mixed-feeding herbivores cannot be clearly distinguished from other dietary groups. These results confirm that combined C, N, and O isotope analyses of a single aliquot of tooth enamel can be used to reconstruct diet and trophic niche. Given its resistance to chemical alteration, the analysis of these three isotopes in tooth enamel has high potential to open new avenues of research in (paleo)ecology and paleontology.